Mount Ijen in the Historical Records of the Dutch East Indies (19th–20th Centuries) - Gema Budiarto; Abdillah Baraas; Edo Suparjan (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2026)
Through historical methods, this study aims to present records of geological studies of Ijen by Western explorers and local Dutch East Indies organizations during the colonial period. The eastern tip of Java is home to many volcanoes. One of them is an active volcano, Mount Ijen. This mountain has amazing natural potential that inspired Westerners to visit and study it. For Western geologists, Ijen is one of the mountains in Java that has received attention as a research object. The main reason is Ijen’s unique and interesting natural potential and phenomena. Local Dutch East Indies organizations concerned with nature conservation also played a role in the study and protection of Ijen. The efforts of Western explorers and local Dutch East Indies nature conservation organizations resulted in fairly detailed studies of Ijen, as well as records of the tragic 1817 eruption and of Ijen’s volcanic activity through 1940.